2009
DOI: 10.1177/0894439309353395
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Willingness to Participate in Mobile Surveys: Exploring the Role of Utilitarian, Affective, Hedonic, Social, Self-Expressive, and Trust-Related Factors

Abstract: Nutzungsbedingungen: Dieser Text wird unter einer Deposit-Lizenz (Keine Weiterverbreitung-keine Bearbeitung) zur Verfügung gestellt. Gewährt wird ein nicht exklusives, nicht übertragbares, persönliches und beschränktes Recht auf Nutzung dieses Dokuments. Dieses Dokument ist ausschließlich für den persönlichen, nicht-kommerziellen Gebrauch bestimmt. Auf sämtlichen Kopien dieses Dokuments müssen alle Urheberrechtshinweise und sonstigen Hinweise auf gesetzlichen Schutz beibehalten werden. Sie dürfen dieses Dokume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 42 publications
0
21
0
3
Order By: Relevance
“…However, this difference may simply be the effect of self-selection of the study population. People who are more positive and satisfied with their lives might be more motivated to participate; previous research has showed that hedonic and affective factors influence people’s willingness to participate in a survey [47]. Also, as we mentioned before, some studies have shown that people who are more educated and affluent are more likely to participate in surveys [30] and high levels of satisfaction with life are linked to high income [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, this difference may simply be the effect of self-selection of the study population. People who are more positive and satisfied with their lives might be more motivated to participate; previous research has showed that hedonic and affective factors influence people’s willingness to participate in a survey [47]. Also, as we mentioned before, some studies have shown that people who are more educated and affluent are more likely to participate in surveys [30] and high levels of satisfaction with life are linked to high income [23].…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating mobile telephones samples into population surveys has brought challenges in both sampling and participation. [ 10 , 11 ] In Australia, there is the difficulty in obtaining a representative sampling frame of mobile telephone numbers since they are rarely listed (7.3% of mobile telephone owners in South Australia are listed). [ 12 ] Several studies in Australia used a random-digit dial (RDD) list of mobile telephone numbers[ 13 , 14 ] but this is compromised as mobile telephone numbers do not include address details or geographical location.…”
Section: Introductionmentioning
confidence: 99%
“…Methods for sampling the mobile-only population, including dual-frame approaches, have received considerable attention (Brick et al, 2006;Tucker, Brick and Meekins, 2007;Tortora, Groves, and Peytcheva, 2008) as have issues of non-response and weighting (Brick et al, 2006;Kennedy, 2007). The acceptability to sample members of being interviewed on their mobile phone has also been studied, mainly with a focus on whether, and in what circumstances, it is possible to achieve good response rates (Bosnjak, Metzger, and Gräf, 2010;Fuchs, 2000;Lau, 2004;Vehovar et al, 2004). Other research has looked more generally at the feasibility and costs of interviewing on mobile phones or at technical aspects such as recording and reporting the outcomes of call attempts .…”
Section: Introductionmentioning
confidence: 99%